Impact of Slow breathing exercise on heart rate variability in male Type 2 diabetes mellitus - Yesmin, Jenefer; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2020)
Background: Reduced heart rate variability (HRV) with cardiac autonomic nerve dysfunction has been found in Type 2 Diabetes Mellitus (T2DM) patients. Yoga based slow breathing exercise (SBE) improved this autonomic functions in healthy subjects. Objectives: To assess the effect of SBE on cardiac autonomic nerve function(CANF) by power spectral analysis of HRV in patients with T2DM. Methods: This prospective interventional study was carried on 30 male diagnosed T2DM patients aged 45-55 years with disease duration 5-10 years enrolled from Out Patient Department of Endocrinology, Bangabandhu Sheikh Mujib Medical University, Dhaka. They performed SBE for 30 minutes twice daily for 3 months. Thirty apparently healthy age, BMI matched male who did not undergo any type of exercise were included as control. To assess the cardiac autonomic nerve function, power spectral analysis of HRV of all patients were done before and after 3 months of SBE. HRV data were recorded by polyrite D (RMS India). For statistical analysis, independent sample and paired sample t-test were used. Results: The preintervention values of Low frequency (LF) normalized unit(nu) and Low frequency/High frequency( LF/HF) ratio were significantly (p<0.001) higher and the values of LF power, HF power, HF normalized unit (HF nu) were significantly (p<0.001) lower in all diabetic patients compared to control. The postintervention values of LF power, HF power, HF nu increased significantly (p<0.001) and the LF nu, LF/HF ratio decreased significantly (p<0.001)compared to their pre-intervention values in T2DM. There were no significant differences between the post intervention values of LF nu, HF nu and LF/HF ratio in T2DM and the control. Conclusion: Impaired cardiac autonomic nerve function was significantly improved by SBE in T2DM. J Bangladesh Soc Physiol. 2019, December; 14(2): 63-68